The Relation Between Physical Activities and the Occurrence of Dysmenorrhea - Adinda Dwi Beauty Fatimah; Fayakun Nur Rohmah (Universitas Ahmad Dahlan, 2020)
Background: According to a research conducted in Palestine, there are 85.1% university students reportedly having pain during menstruation. The occurrence of dysmenorrhea in Indonesia is 86%. The high occurrence of dysmenorrhea has less attention from the public and even from the adolescents themselves. One of the factors that influence the occurrence of dysmenorrhea is physical activities. Women who do not do exercise regularly have 3.48 times of risk to experience dysmenorrhea. This study aims to reveal the correlation between physical activities and dysmenorrhea. Method: This was quantitative research with cross sectional design. The population in this study was 136 female students of D4 Medical Laboratory Technology study program. Sixty eight respondents were contributed in this study with exclusion and inclusion criteria. The sampling technique used was total sampling. Bivariate analysis used was the Fisherâ€™s Exact correlation test. The research hypothesis was there was a correlation between physical activities and the occurrence of dysmenorrhea. Results: There were 51 respondents who experienced dysmenorrhea (75%) and there were 53 respondents who were categorized at moderate physical activities obtained p < 0.05). Conclusion: Â It can be concluded that there is a relation between physical activities and dysmenorrhea